Analisis Daya Dukung Pada Tanah Gambut Dan Lanau Menggunakan Cerucuk Kayu Mahang - Fajrian Saddek; Muhardi Muhardi; Ferry Fatnanta (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Soft soil is one of the soil type with low bearing capacity. Generally the problem that arises in the construction on soft soil is sliding. An attempt to improve low shear resistivity of soft soil can be accomplished through soil reinforcement methods. One of the method is by using wooden pile as foundation. Wooden pile can be resembled as a shortpile, one of a foundation type that widely used in soft soil layer especially to bear a large amount load.This research was conducted through laboratory scale model approach method, but the behavior was made to resemble actual behavior in the field. Wooden pile type that will be used in this research is Mahang Wood and will be installed on peat soil and silt soil. Variations of installed wooden pile are 1 pile, 4 pile, and 9 pile with each pile divided into pile with bark and pile without bark. It is also varied with installation of piles for 1 day and 7 day. It is hoped that such small-scale behavior will result in additional theories of reinforcement in soft soil.The result of this research is the increasing of soil bearing capacity along with the addition of pile number. The bark of the wood pile also affects the bearing capacity. Increased bearing capacity occurs from 1 day to 7 day installation.Keywords : bearing capacity, wooden pile, soft soil, peat, silt